A Rábca Abda-Győr közötti szakaszának természetvédelmi szempontú botanikai felmérése - Pallás Anna Ildikó (2015)
The botanical surveying of the Rábca between Abda-Győr from the nature conservation point of view. During making the essay, I made an effort to survey the habitat status of the land. I took into consideration the found protected species of plants. I made usage proposals and remarks for the affected areas. By the field surveying, realized that most of the habitats are in medium naturalness status. The precious mesotropich wet meadow is in extremely good naturalness status. In my essay I tried to find connections between the habitats and the protected plants. I found on the Rábca the rare and interesting Orobanche reticulata.